A method for simultaneously realizing boron-aluminum dual-doping / dual-coating and ultra-high nickel cobalt-free cathode material with long cycle stability at high rate

By performing boron-aluminum double-doping/double-coated treatment on ultra-high nickel cobalt-free cathode material, the problem of poor cyclic stability of the material at high magnification is solved, and the rate performance and cyclic stability of the material are significantly improved.

CN117374249BActive Publication Date: 2025-02-21GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311419579.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-02-21
Estimated Expiration
2043-10-30

AI Technical Summary

Technical Problem

Ultra-high nickel cobalt-free cathode material has poor cycling stability at high magnifications, resulting in unstable material structure and interface corrosion, affecting the battery's range and circulation capacity.

Method used

The method of synchronously realizing boron-aluminum double-doping/double-coated is used to improve the electronic conductivity and layering of the material by coating the fast ion conductor of lithium metaborate and lithium metaborate and the coordinated doping of aluminum ions and boron ions. Structural stability.

Benefits of technology

It effectively improves the long cycle stability and rate performance of ultra-high nickel cobalt-free cathode materials at high magnifications, and extends the battery's cycle capacity retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117374249B_ABST
    Figure CN117374249B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for realizing a co-doping / co-coating of boron and aluminum simultaneously and having long cycle stability at high rates for an ultra-high nickel cobalt-free cathode material. The boron / aluminum is first uniformly coated on the surface of the material by a hydrothermal method, and then annealed in an oxygen atmosphere in a tubular furnace. The lithium residue on the surface of the ultra-high nickel cobalt-free cathode material is used as a raw material. After an in-situ reaction at high temperature, not only the harmful lithium residue on the surface of the material is effectively removed, but also a lithium metaborate / lithium metaaluminate dual fast ion conductor coating layer is formed at the same time. The fast ion conductor effectively improves the stability and ionic conductivity of the material surface / interface. Secondly, the co-doping of the dual ions formed by thermal diffusion of aluminum ions and boron ions at high temperatures effectively improves the electronic conductivity of the material and the stability of the layered structure. Therefore, the co-doping / co-coating of boron and aluminum simultaneously plays a vital role in effectively improving the rate performance and cycle stability of the ultra-high nickel cobalt-free cathode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion battery materials, and in particular to a method for simultaneously realizing boron-aluminum dual doping / dual coating and having ultra-high nickel cobalt-free cathode material with long cycle stability at high rates. Background Art

[0002] The electric vehicle market is developing rapidly under the dual drive of policy and consumption. The production of electric vehicles is growing exponentially. The market urgently needs to continuously increase the supply of low-cost, high-performance lithium-ion batteries. Increasing the driving range is one of the biggest challenges for the commercialization of electric vehicles, which needs to start with the energy density of the battery. Among the nickel-cobalt-manganese ternary positive electrode materials, the high-nickel ternary positive electrode material NCM811 has been studied more and has achieved some results. However, the energy density of NCM811 can only reach 760 Wh / kg, which cannot achieve a driving range of more than 300 miles. If the nickel content is further increased to more than 90% (ultra-high nickel ternary positive electrode material), the energy density will reach more than 800 Wh / kg, which can meet people's demand for more than 300 miles. However, there is still little research on ultra-high nickel ternary positive electrode materials, because ultra-high nickel exacerbates the irreversible changes in the crystal phase structure such as cation mixing, lattice collapse, oxygen evolution, and interface side reactions, resulting in very poor stability of the material crystal structure and cycle stability.

[0003] Both high-nickel ternary cathode materials and ultra-high-nickel ternary cathode materials use cobalt. Due to cobalt's toxicity, low abundance in the earth's crust, and more than 90% import dependence, it is considered to be the material with the highest risk in the short- and medium-term electric vehicle material supply chain. Eliminating cobalt has become an urgent need for the automotive industry. Ultra-high nickel cobalt-free cathode materials (LiNi 0.9 Mn 0.1 O 2 ) has become one of the most promising cathodes for next-generation lithium-ion batteries due to its high energy density and low cost.

[0004] As lithium-ion cathode materials develop towards high nickel and cobalt-free, the cycling stability of the materials has deteriorated dramatically. This is mainly due to the following reasons: (1) Cobalt can effectively stabilize the structure of the material. When the battery material without cobalt is charged and discharged at a high rate, the electrode material is severely polarized. The uneven deintercalation of lithium ions leads to irregular stress, which causes the material to crack, pulverize, and release oxygen, resulting in a sharp decrease in the cycling capacity of the material at a high rate. (2) Since the material is directly exposed to the electrolyte, H 2 O and LiPF 6 The generated HF corrodes the interface of the positive electrode material and dissolves the transition metal. The transition metal migrates to the negative electrode and is reduced to metal, causing the SEI film to consume lithium ions and electrolyte molecules during repeated charging and discharging.

[0005] In view of the problems faced by ultra-high nickel cobalt-free cathode materials, surface coating of the materials can improve the ionic conductivity and surface / interface structural stability of the surface / interface. At the same time, the selection of appropriate ion doping can promote the electronic conductivity and layered structure stability of the material. Therefore, the implementation of both internal and external improvements will effectively improve the rate performance and cycle stability of ultra-high nickel cobalt-free cathode materials. Based on the limitations of the traditional single element modification function, we adopted a method of simultaneously realizing boron-aluminum dual doping and dual coating, which effectively promoted the long-term cycle stability of ultra-high nickel cobalt-free cathode materials at high rates. Since lithium metaborate and lithium metaaluminate are fast ion conductors themselves, the use of this dual fast ion conductor coating can effectively improve the surface / interface stability and ionic conductivity of the material. Secondly, the simultaneous synergistic doping of aluminum ions and boron ions can effectively improve the electronic conductivity and layered structure stability of the material. The effective synergy of the two provides an effective solution to the key problems of poor cycle stability and rate performance of ultra-high nickel cobalt-free cathode materials. Summary of the invention

[0006] The purpose of the present invention is to: in view of the above-mentioned problems, the present invention provides a method for simultaneously achieving boron-aluminum dual doping / dual coating and ultra-high nickel cobalt-free cathode material with long cycle stability at high rates.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A method for designing an ultra-high nickel cobalt-free cathode material that simultaneously realizes boron-aluminum dual doping / dual coating and has long cycle stability at high rates comprises the following steps:

[0009] S1. Preparation of ultra-high nickel cobalt-free cathode material blank sample

[0010] The lithium source and the ultra-high nickel cobalt-free precursor are weighed in a molar ratio of 1:1.01-1:1.08, and the mixture is repeatedly ground for 30-90 minutes until the mixture is uniformly mixed to obtain a first mixture, and the first mixture is placed in a tube furnace, and a gradient calcination technique is used in an oxygen atmosphere to obtain an ultra-high nickel cobalt-free cathode material blank sample;

[0011] The temperature control conditions of the gradient calcination are: heating to 300-700°C at a heating rate of 1-10°C / min, keeping warm for 3-6 hours, then heating to 750-780°C at a heating rate of 1-10°C / min, keeping warm for 10-18 hours;

[0012] S2. Preparation of ultra-high nickel cobalt-free cathode materials with boron-aluminum dual doping / dual coating and long cycle stability at high rates;

[0013] The blank sample, the boron source and the aluminum source are weighed in a molar ratio of 1:0.005-1:0.02, the weighed ultra-high nickel cobalt-free cathode material blank sample is dispersed in anhydrous ethanol to obtain solution 1, the weighed boron source and the aluminum source are dispersed together in anhydrous ethanol to obtain solution 2, and then solution 1 and solution 2 are ultrasonically dispersed for 1-2 h;

[0014] After ultrasonication, solution 1 is heated to about 80°C in a water bath, and solution 2 is slowly dripped into the high-speed stirred solution 1. After the addition, the water bath temperature is lowered to about 40°C and stirred for 6-12 h, and then the temperature is raised to about 80°C and stirred until the anhydrous ethanol solution is completely evaporated. Finally, it is placed in a 120°C oven and dried for 3-12 h to obtain a dry material, and the stirring speed is 300-3000 rpm;

[0015] Place the dry material in a tubular furnace, heat it to 500-700°C at a heating rate of 1-10°C / min in an oxygen atmosphere, and keep it warm for 4-8 hours to obtain an ultra-high nickel cobalt-free cathode material that simultaneously achieves boron and aluminum dual doping / dual coating and has long cycle stability at high rates.

[0016] The beneficial effects of the present invention are: the ultra-high nickel cobalt-free cathode material that realizes boron-aluminum dual doping / dual coating simultaneously and has long cycle stability at high rates does not require the addition of an additional lithium source, but instead utilizes the residual alkali on the surface of the cathode material to form lithium aluminate and lithium borate fast ion conductors in situ on the surface of the material, effectively improving the stability and ionic conductivity of the material surface / interface. Secondly, the dual ion synergistic doping formed by thermal diffusion of aluminum ions / boron ions is simultaneously realized at high temperatures, effectively improving the electronic conductivity of the material and the stability of the layered structure. Therefore, the synchronously realized boron-aluminum dual doping / dual coating can effectively improve the rate performance and cycle stability of the ultra-high nickel cobalt-free cathode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image of a blank sample of the ultra-high nickel cobalt-free cathode material prepared in the step of Example 1 of the present invention;

[0018] Figure 2 This is a scanning electron microscope image of the ultra-high nickel cobalt-free cathode material with a boron-aluminum double coating / double doping amount of 0.5 mol% each prepared in the step of Example 2 of the present invention;

[0019] Figure 3 This is a scanning electron microscope image of the ultra-high nickel cobalt-free cathode material with a boron-aluminum double coating / double doping amount of 0.75 mol% each prepared in the step of Example 3 of the present invention;

[0020] Figure 4This is a comparison chart of the discharge specific capacity of the ultra-high nickel cobalt-free cathode material prepared in the steps of Example 1, Example 2, and Example 3 of the present invention at an ambient temperature of 25° C., a cut-off voltage of 2.8-4.4 V, and a cycle rate of 5 C for 300 cycles;

[0021] Figure 5 This is a comparison chart of the discharge specific capacity of the ultra-high nickel cobalt-free cathode material prepared in the steps of Example 1, Example 2, and Example 3 of the present invention at an ambient temperature of 25° C., a cut-off voltage of 2.8-4.3 V, and different rates. DETAILED DESCRIPTION

[0022] The specific implementation mode of the present invention is described below in conjunction with the examples, but the following examples are only used to explain the present invention in detail and do not limit the scope of the present invention in any way. The equipment components involved in the following examples are all conventional equipment components unless otherwise specified; the industrial raw materials involved are all commercially available conventional industrial raw materials unless otherwise specified. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. In addition, the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0023] The following comparative example 1 is an example of an ultra-high nickel cobalt-free cathode material prepared by a conventional calcination method; Example 2 and Example 3 are examples of the present invention, and the ultra-high nickel cobalt-free cathode materials prepared by Example 1 and Example 2 and Example 3 of the present invention are characterized and analyzed, and the analysis method includes:

[0024] 1. Scanning electron microscope (SEM) test: Scanning electron microscope, instrument model: SU5000;

[0025] 2. Assembly and testing of CR2025 button cells: Ultra-high nickel cobalt-free cathode material (the final product prepared in Example 1, Example 2 and Example 3), conductive carbon black (Super-P), and polyvinylidene fluoride (PVDF) were made into a slurry in a mass ratio of 8:1:1 and coated on an aluminum foil. The dried aluminum foil loaded with the slurry was cut into small discs with a diameter of about 12 mm using a cutting machine as the positive electrode. A metal lithium sheet was used as the negative electrode, Celgard2500 was used as the diaphragm, and a 1 M carbonate solution was used as the electrolyte (wherein the solvent was a mixed solution of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a volume ratio of 1:1:1, and the solute was LiPF6). The CR2025 button cells were assembled in an argon atmosphere glove box.

[0026] Example 1 (unmodified)

[0027] Lithium hydroxide monohydrate and Ni0.9Mn0.1(OH)2 precursor were weighed at a molar ratio of 1.05:1 to obtain 1 g Ni 0.9 Mn 0.1 (OH) 2 The precursor and 0.4873 g of lithium hydroxide monohydrate were placed in a mortar and mixed until uniform, and the uniformly mixed material was placed in a tube furnace in an oxygen atmosphere for calcination. The temperature was first raised to 500°C at a heating rate of 5°C / min and kept for 5 h; then the temperature was raised to 750°C at a heating rate of 5°C / min and kept for 15 h, and then cooled naturally. The cooled material was crushed to obtain an ultra-high nickel cobalt-free cathode material.

[0028] This embodiment 1 is used as a control group, and the cathode material (LiNi 0.9 Mn 0.1 O 2 )The SEM image of the blank sample is as follows Figure 1 As shown. It can be seen that LiNi 0.9 Mn 0.1 O 2 The surface of the cathode material is not coated, and the positive electrode material particles are spherical and have a smooth surface.

[0029] Example 2 (boron and aluminum molar percentages are each 0.5%)

[0030] S2. Prepare an ultra-high nickel cobalt-free cathode material that simultaneously achieves boron-aluminum dual doping / dual coating and has long cycle stability at high rates.

[0031] The blank sample prepared in Example 1, the boron source, and the aluminum source were weighed in a molar ratio of 1:0.005. 0.9 Mn 0.1 O 2 The solution 1 was dispersed in anhydrous ethanol to obtain a solution 1, 0.003 g of boric acid and 0.0193 g of aluminum nitrate nonahydrate were dispersed in anhydrous ethanol to obtain a solution 2, and then the solution 1 and the solution 2 were ultrasonically dispersed for 1 h;

[0032] After ultrasound, solution 1 was heated to 80°C in a water bath, and solution 2 was slowly dripped into the high-speed stirred solution 1. After the addition, the water bath temperature was lowered to 40°C and stirred at a low speed for 12 h. Then the temperature was raised to 80°C and stirring was continued until the anhydrous ethanol solution was completely evaporated. Finally, the dried material was placed in a 120-degree oven for 3 h to obtain a dry material.

[0033] The dry material is placed in a tubular furnace, heated to 700°C at a heating rate of 5°C / min in an oxygen atmosphere, and kept warm for 4 hours to obtain an ultra-high nickel cobalt-free cathode material that simultaneously achieves boron and aluminum dual doping / dual coating and has long cycle stability at high rates.

[0034] The SEM image of the cathode material synthesized in Example 2 is as follows Figure 2 As shown, it can be seen that the particles are spherical. Compared with the cathode material synthesized in Example 1, the surface of the material becomes rough and the coating material is obviously present.

[0035] Example 3 (boron and aluminum molar percentages are 0.75% each)

[0036] The blank sample prepared in Example 1 was weighed with the boron source and the aluminum source in a molar ratio of 1:0.0075, 1 g of LiNi0.9Mn0.1O2 was dispersed in anhydrous ethanol to obtain solution 1, 0.0046 g of boric acid and 0.0286 g of aluminum nitrate nonahydrate were dispersed in anhydrous ethanol to obtain solution 2, and then solution 1 and solution 2 were ultrasonically dispersed for 1 h;

[0037] After ultrasonication, solution 1 was heated to 80°C in a water bath, and solution 2 was slowly dripped into the high-speed stirred solution 1. Then, the water bath temperature was lowered to 40°C and stirred at a low speed for 12 h. Then, the temperature was raised to about 80°C and stirred until all the anhydrous ethanol was evaporated. Finally, the mixture was placed in an oven at 120°C for 3 h to obtain a dry material.

[0038] The dry material is placed in a tubular furnace, heated to 700°C at a heating rate of 5°C / min in an oxygen atmosphere, and kept warm for 4 hours to obtain an ultra-high nickel cobalt-free cathode material that simultaneously achieves boron and aluminum dual doping / dual coating and has long cycle stability at high rates.

[0039] The SEM image of the cathode material synthesized in Example 3 is as follows: Figure 3 As shown, it can be seen that the particles are still spherical, and the surface of the cathode material synthesized in Comparative Example 2 is rougher and the surface coating material is more obvious.

[0040] The comparison of the electrochemical performance of the ultra-high nickel cobalt-free cathode material before and after modification is as follows:

[0041] The materials obtained in Example 1, Example 2 and Example 3 were subjected to cycle tests at an ambient temperature of 25°C, a cut-off voltage of 2.7-4.4 V and a rate of 5 C. The cycle test results are shown in FIG. Figure 4As shown, the first-cycle discharge specific capacities of Example 1, Example 2, and Example 3 are 174.6 mAh / g, 181.4 mAh / g, and 182.7 mAh / g, respectively. After 300 cycles, the discharge specific capacities are 60.4 mAh / g, 136.7 mAh / g, and 146.7 mAh / g, respectively, and the capacity retention rates are 34.5%, 75.3%, and 80.2%, respectively. By comparison, it can be seen that both the first-cycle discharge specific capacity and the cycle capacity retention rate after 300 cycles of Example 2 and Example 3 are significantly higher than those of Example 1. The materials obtained in Example 1, Example 2, and Example 3 were subjected to rate performance tests at an ambient temperature of 25°C, a cut-off voltage of 2.7-4.3V, and different rates. The test results are shown as follows. Figure 5 As shown in the figure, as the rate increases, the difference in discharge specific capacity between Example 1, Example 2 and Example 3 at the same rate gradually increases. Figure 4 Long cycle performance test at high rate and Figure 5 Rate performance tests at different rates have proved that the boron-aluminum dual-doped / double-coated ultra-high nickel cobalt-free cathode material can effectively solve the key problems of long-term cycle stability and poor rate performance of ultra-high nickel cobalt-free cathode materials at high rates.

[0042] The present invention has been described in detail above in conjunction with the embodiments. However, those skilled in the art will appreciate that, without departing from the spirit of the present invention, the specific parameters in the above embodiments may be changed to form a plurality of specific embodiments, which are all within the common variation range of the present invention and will not be described in detail herein.

Claims

1. A method for simultaneously achieving boron-aluminum dual doping / dual coating and ultra-high nickel cobalt-free cathode material with long cycle stability at high rate, characterized in that: The following steps are involved: S1. Preparation of ultra-high nickel cobalt-free cathode material blank sample Weigh appropriate amounts of ultra-high nickel cobalt-free precursor and lithium source according to a molar ratio of 1:1.01-1:1.08, grind repeatedly for 30-90 minutes until mixed evenly to obtain a first mixture, place the first mixture in a tube furnace, and use a gradient calcination technology under an oxygen atmosphere to obtain an ultra-high nickel cobalt-free cathode material blank sample; The ultra-high nickel cobalt-free precursor is Ni 0.9 Mn 0.1 (OH)2; The temperature control conditions of the gradient calcination are: heating to 300-700°C at a heating rate of 1-10°C / min, keeping warm for 3-6h, then heating to 750-780°C at a heating rate of 1-10°C / min, keeping warm for 10-18h; S2. Prepare ultra-high nickel cobalt-free cathode materials that are simultaneously doped with boron and aluminum and have long cycle stability at high rates; The ultra-high nickel cobalt-free cathode material blank sample, the boron source, and the aluminum source are weighed in a molar ratio of 1:0.005-1:0.02, and the weighed ultra-high nickel cobalt-free cathode material blank sample is dispersed in anhydrous ethanol to obtain solution 1, and the weighed boron source and aluminum source are dispersed together in anhydrous ethanol to obtain solution 2, and then solution 1 and solution 2 are ultrasonically dispersed for 1-2 hours respectively; After ultrasonication, solution 1 is heated to 80°C in a water bath, and solution 2 is slowly dripped into solution 1 which is stirred at high speed. After the addition, the water bath temperature is lowered to 40°C and stirring is continued for 6-12h, and then the temperature is raised to 80°C and stirring is continued until the anhydrous ethanol solution is completely evaporated. Finally, the mixture is placed in a 120°C oven and dried for 3-12h to obtain a dry material, and the stirring speed is 300-3000rpm. Place the dry material in a tubular furnace, heat it to 500-700°C at a heating rate of 1-10°C / min in an oxygen atmosphere, and keep it warm for 4-8 hours to obtain an ultra-high nickel cobalt-free cathode material that simultaneously achieves boron and aluminum dual doping / dual coating and has long cycle stability at high rates.

2. A method for simultaneously achieving boron-aluminum dual-doping / dual-coating and ultra-high nickel cobalt-free cathode material with long cycle stability at high rates according to claim 1, characterized in that: The lithium source in step S1 is one or more of lithium hydroxide, lithium carbonate, and lithium nitrate.

3. The method of claim 1 for simultaneously realizing a boron-aluminum dual-doping / dual-coating ultra-high nickel cobalt-free cathode material having long cycle stability at high rates, characterized in that: The boron source in step S2 is at least one of lithium borate, lithium metaborate and borohydride; the aluminum source in step S2 is aluminum nitrate nonahydrate or aluminum isopropoxide.

4. An ultra-high nickel cobalt-free cathode material that achieves simultaneous boron-aluminum dual doping / dual coating and has long cycle stability at high rates, characterized in that: Prepared by the method according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • High-nickel NCM ternary positive electrode material with surface coated with multiple substances simultaneously and application of high-nickel NCM ternary positive electrode material

    CN114975914A

  • Preparation method of LiBO2 / LiAlO2 double-layer coated modified lithium ion battery quaternary positive electrode material

    CN115196693A